Zemljepisnojezikoslovna členitev kajkavščine ter slovensko-kajkavska jezikovna meja - Šekli, Matej (Slovenski jezik, 2013)
In the article a critical survey is given of the criteria employed in the geo-linguistic delimitation of Kajkavian - an idiom of Central South Slavic (in Croatian srednjojužnoslavenski ) - from the other Western South Slavic idioms (Slovene, Čakavian, Štokavian) as well as its subdivision into dialects, as presented in Croatistic dialectological and historical linguistic literature. We aim to determine the defining characteristics of Kajkavian in general, especially in relation to Slovene, and the defining characteristics of the individual Kajkavian dialects, which in turn provides the basis for further genetic linguistic analysis of some marginal local dialects on the Kajkavian-Slovene language border. These are defined as "distinctive" in Croatistic dialecto - logical literature. The working hypothesis is verified that these "distinctive marginal Kajkavian local dialects" are, in the genetic-linguistic sense, in fact part of the diasystem of the Slovene language.
Keywords: Croatian; dialect; genetolingvistika; hrvaščina; jezikovne meje; kajkavščina; narečja; Slovene; slovenščina